Awareness and Perceptions of Farmers about Water Pollution in Rajasthan - Gargi Bhatt; Aravindh Kumar (Journal of Extension Education)
This study assessed 120 farmers’ awareness and perceptions of water pollution in Udaipur district of Rajasthan, India using Latent Class Analysis (LCA). Findings revealed that most of the farmers had low legal literacy (67.50%), with limited awareness on laws such as the Environment Protection Act, 1986, and the Water (Prevention and Control of Pollution) Act, 1974. While 85.83 per cent perceived visible effects of water pollution, such as foul smells, only 13.33 per cent were aware of specific legal frameworks. Television and social media emerged as primary information sources. The study highlights the need for targeted legal literacy programmes to empower farmers in addressing water pollution issues.